The aesthetic wievs of Grigor Tatevatsi - Zakaryan, Seyran (Bulletin of Yerevan University E: Philosophy, Psychology, 2023)
The article analyzes the aesthetic views of Saint Grigor Tatevatsi (1346-1409), a famous theologian-philosopher of Tatev University, in the context of his theological-metaphysical, epistemological, anthropological and moral understandings. Tatevatsi's aesthetic views, teaching about beauty, art, craft, divine and human creation are based on the principles of the religious-theological worldview (monotheism, creationism, superiority of the spiritual over the material-sensual sphere, symbolism, allegory etc.) and philosophical understandings consistent with them or adapted to them. Tatevatsi's aesthetic views have a synthetically nature, which is due to the principle of non-differentiation of the spheres of spiritual activity characteristic of medieval thinking. He distinguishes supernatural/divine and natural/human beauties, different degrees of beauty in the created world, values ​​and allegorically interprets earthly beauties, ascribes beauty to objective, interconnected and complementary properties: perfection, moderation, proportion, purity (shine, color, light), harmony and integrity. Apart from the objective qualities, the beautiful also has a subjective coloring, which is related to the cognitive and evaluation abilities of a person. Tatevatsi's perception of beauty is closely related to moral understandings of good and evil, beautiful and ugly, the meaning and purpose of human life. He identifies the good with the beautiful and the evil with the ugly. In general, Tatevatsi supports the aesthetic theory according to which, although the beautiful and true creation is in the divine world and the spiritual sphere, earthly beauties and human art and craft are valued along with spiritual beauties.
Keywords: Grigor Tatevatsi; medieval worldview; symbolism; allegory; aesthetics; beautiful; objective and subjective properties of beautiful; art and craft; creativity